Liquid Chromatography-Tandem Mass Spectrometry Analysis of Perfluorooctane Sulfonate and Perfluorooctanoic Acid in Fish Fillet Samples - Viviana Paiano; Elena Fattore; Andrea Carrà; Caterina Generoso; Roberto Fanelli; Renzo Bagnati (Journal of Analytical Methods in Chemistry)
Perfluorooctane sulfonate (PFOS) and perfluorooctanoic (PFOA) acid are persistent contaminants which can be found in environmental and biological samples. A new and fast analytical method is described here for the analysis of these compounds in the edible part of fish samples. The method uses a simple liquid extraction by sonication, followed by a direct determination using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The linearity of the instrumental response was good, with average regression coefficients of 0.9971 and 0.9979 for PFOS and PFOA, respectively, and the coefficients of variation (CV) of the method ranged from 8% to 20%. Limits of detection (LOD) were 0.04 ng/g for both the analytes and recoveries were 90% for PFOS and 76% for PFOA. The method was applied to samples of homogenized fillets of wild and farmed fish from the Mediterranean Sea. Most of the samples showed little or no contamination by perfluorooctane sulfonate and perfluorooctanoic acid, and the highest concentrations detected among the fish species analyzed were, respectively, 5.96 ng/g and 1.89 ng/g. The developed analytical methodology can be used as a tool to monitor and to assess human exposure to perfluorinated compounds through sea food consumption.